Exploring the usefulness of the Brief COPE in clinical and positive psychology: A discriminant content validity study - Siaputra, Ide Bagus; Rasyida, Afinnisa; Ramadhanty, Amanda Meuthia; Triwijati, Noeroel Kentjono Endah (Psikohumaniora: Jurnal Penelitian Psikologi, 2023)
The Brief Coping Orientation to Problem Experienced (COPE) scale is widely used for measuring coping strategies. However, concerns persist regarding the dimensions captured by the scale and the accuracy of item representation. This study examined the relevance of adapted Brief COPE items using discriminant content validity (DCV). A panel of experts (n = 15) assessed the extent to which the items corresponded to their intended dimensions. Intraclass correlation (ICC) estimates ranged from 0.640 to 0.828, indicating agreement among experts. A one-sample t-test evaluated DCV, revealing that 21 out of 28 items distinctly and exclusively measured intended dimensions, confirming their discriminant content validity. Seven items were excluded: three did not measure coping strategies (non-dimension), and four measured them in different dimensions (wrong-dimension). The discriminant content-validated Brief COPE scale improves coping assessment, benefiting psychological therapies and providing researchers with refined measures for each coping strategy dimension, addressing dimensional concerns.